The The Relationship Of Stress Level And Menstrual Cycle In Adolescent Girls At Manbatul Akhlaq Mojo Kediri Islamic Boarding School - Tety Ripursari; Nita Dwi Astikasari; Candra Wahyuni (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2024)
Adolescent girls especially female students, as academic individuals cannot be separated from stress in daily activities. As result of perceveid stress, it can cause the putiaitary to release ACTH wich then increases cortisol levels, causing disruption of the menstrual cycle. The aim of this research was to determine the relationship between stress levels and the menstrual cycle in adolescent girls at the Manbatul Akhlaq Mojo Kediri Islamic Boarding School. This research uses an observational analytical research design with a cross sectional approach. Purposive sampling technique. The sample was 32 respondents, statistical tests used spearmen-Rho. The results of the reserch from 32 respondents showed that the majority of respondents who experienced moderate levels of stress had irregular menstrual cycles (<21 or >35 days) with a precentage of 16 people (50%) and respondents who experienced moderate levels of stress had regular menstrual cycles (21-35 days) There were 2 people with a percentage (6.25%), respondents with mild levels of stress had irreguler menstrual cycles totaling 5 people (15.6%), and respondents with low levels of stress had regular menstrual cycles as many as 9 people(28,1%). There is sigifict reltioship etwee stress d the menstrual cycle in adolescent girls the Mamtul Akhlaq Mojo Kediri Islamic Boarding School. P=0.001<0.05. You need to get enough rest, joke and tell stories to friends, do fun things, do physical activity/exercise, so that the stress felt by respondents can be minimized and their menstruation becomes regular.